Adsorption of hydrocarbons on FCC catalysts under reaction conditions - de la Puente, Gabriela (2005)
A modified CREC Riser Simulator reactor was used in order to assess tne adsorption constants of various hydrocarbons produced in the cracking of n-hexadecane over an equilibrium commercial FCC catalyst at 550°C. Complementary experiments were performed with n-hexane on both the same catalyst and a pure HY zeolite. A method to estimate apparent hydrocarbon adsorption constants, based on mass balances, the assumption of Henry's law-type behavior, and the compositions observed in two samples, was proposed. One sample was collected immediately after reaction, representing the gas phase that is in equilibrium with the catalysts, and the other one included adsorbed hydrocarbons. It was shown that when a mixture of hydrocarbons produced by cracking reactions contacts the catalysts, there exists a selective enhancement in the adsorption of those hydrocarbons that individually adsorb more strongly. Additional experiments with simple mixtures and no chemical reaction confirmed these observations. Evidence suggests that the diffusive mass transport process in the catalyst particles plays an important role.